Epidural Administration New Perspectives and Uses - Fyneface-Ogan, Sotonye (IntechOpen, 2023)
Epidural administration is used by physicians and nurse anesthetists to administer local anesthetic agents, analgesics, and diagnostic medicines such as radiocontrast agents, glucocorticoids and other medicines. The epidural administration of medication has made some aspects of clinical practice much more accessible. This book focuses on various aspects of epidural administration, from methods to clinical uses, and its diverse applications. The book will be a valuable asset for anaesthesiologists, paediatricians, radiologists, internists, and intensivists in active clinical practice, including medical students and practitioners undergoing residency training.